Effect of Lime Juice (Citrus Aurantifolia) on Blood Urea Nitrogen and Creatinine Levels in Wistar Rats Induced by Gentamicin - Queen Nurul Sufi; Hartalina Mufidah; Ahdiah Imroatul Muflihah; Sholihatil Hidayati (Universitas Muhammadiyah Surakarta, 2025)
Gentamycin is an antibiotic that has the effect of acute kidney failure. Increased levels of BUN and Creatinine can characterize acute kidney failure. Lime juice (Citrus aurantifolia) contains flavonoid compounds as antioxidants that can regenerate kidney function. This study aims to determine the difference in BUN and Creatinine levels before and after being given lime juice. This study uses an experimental study design with a pretest-postest design. In the model mice, gentamicin was induced at a dose of 60 mg/KgBB for 10 days, and then BUN and creatinine levels were checked. This study was divided into 5 groups, including the negative, healthy, and treatment groups 1, 2, and 3, with a dose of lime juice 0.5 ml/KgBB, 1.0 ml/KgBB, and 1.5 ml/KgBB. The results showed that the average change in BUN levels before and after between groups was significant (sig < 0.05), and the average change in creatinine levels before and after between groups was significant (sig < 0.05). This study concluded that the average decrease in BUN levels in treatment group 3 was significant by 7.9 mg/dl, and the average decrease in creatinine levels in treatment groups 2 and 3 was significant by 0.8 mg/dl.